Where do I belong: alienation as a psychological struggle of the characters in lahiri's the namesake 2003 - Yahya, Salam Hussein; Mani, Manimangai (Universidad Técnica de Manabí, 2022)
Alienation is an inevitable aspect of the modern life. Due to the rapid changes in culture, societies, technology and most importantly, psychological science, myriads of people in the contemporary era are alienated. However, the phenomenon of alienation is not new, it has been there for quite a while, but was not given or announced publicly. Anytime anyone oppresses some of their desires and/or attempts to hide aspects of their real lives, they feel alienated and isolated from this world. Further, the more conspicuous consequences of alienation and the name came to prominence after the ruthless process of colonization. It was owing to this heartless segregation among the races and cultural or ethnic discrimination that alienation surfaced publically and the authors and/or intellectuals commenced to address it. Among them Lahiri deserves a lion’s share for her novel the Namesake. She logically and smartly portrays the psychological status of her characters and shows the bitter consequences of alienation through her depiction of the novel’s main characters. The paper thus attempts to focus on the problems of alienation and how the characters in the Namesake experience it.